Lake Victoria Monitored from Space - Awange, Joseph (Springer Nature, 2020)
This book employs a suite of remotely sensed products and advanced technologies to provide the first comprehensive space-based sensing of Lake Victoria, the world’s second largest freshwater lake that supports a livelihood of more than 42 million people, modulates regional climate, but faces myriads of challenges. Proper understanding of the lake and changes in its physical dynamics (e.g., water level, shorelines and areal dynamics) resulting from the impacts of climate variation and climate change as well as anthropogenic (e.g., hydropower and irrigation) is important for its management as well as for strategic development before, during and after climate extremes (e.g., floods and droughts) in order to inform policy formulations, planning and mitigation measures. Owing to its sheer size, and lack of research resources commitment by regional governments that hamper its observations, however, it is a daunting task to undertake studies on Lake Victoria relying solely on in-situ “boots on the ground” measurements, which are sparse, missing in most cases, inconsistent or restricted by governmental red tapes. The book is useful to those in water resources management and policy formulations, hydrologists, environmentalists, engineers and researchers.